Analisis Yuridis terhadap Perkawinan Perempuan Muallaf dengan Wali Nikah Tokoh Agama: (Studi atas Penetapan Nomor 20/Pdt.P/2012/PA.Smi dan Penetapan Nomor 6/Pdt.P/2013/PA.Sgr) - Makbul Bakari; Rizal Darwis (Al-Mizan (e-Journal), 2019)
This research discusses to study and analyze the legal considerations of the Panel of Judges' judgments in Stipulation Number 20/Pdt.P/2012/PA.Smi and Stipulation Number 6/Pdt.P/2013/PA.Sgr. about itsbāt nikah in marriage of muallaf women with marriage guardians of religious leaders, then comparing the results of the two determinations. This research is a type of library research that acts descriptive-analytical-comparative. The choices used are juridical-normative and syara. The results of this study indicate that the contextual interpretation of the legal text more fulfills a sense of justice in favor of textual interpretation. Stipulation Number 6/Pdt.P/2013/PA.Sgr. which departs from contextual interpretation by considering socio-cultural and legal awareness of the community and contra legem by way of questioning the meaning (supported legal interpretation) of terminology). Honower Stipulation Number 20/Pdt.P/ 2012/PA.Smi which starts from textual-legalistic interpretation cannot fulfill the sense of justice of the community, but can only fulfill procedural demands.